2016
DOI: 10.1093/infdis/jiw232
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring for Human Papillomavirus Vaccine Impact Among Gay, Bisexual, and Other Men Who Have Sex With Men—United States, 2012–2014

Abstract: Background Gay, bisexual, and other men who have sex with men (MSM) are at high risk for human papillomavirus (HPV) infection; vaccination is recommended for US males, including MSM through age 26 years. We assessed evidence of HPV among vaccine-eligible MSM and transgender women to monitor vaccine impact. Methods During 2012–2014, MSM aged 18–26 years at select clinics completed a computer-assisted self-interview regarding sexual behavior, human immunodeficiency virus (HIV) status, and vaccinations. Self-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 45 publications
1
39
1
2
Order By: Relevance
“…22 However, a recent study among 922 vaccine-eligible gay, bisexual, and other MSM aged 18–26 years in 2 US cities demonstrated that while 90.9% of HIV-positive young MSM and 62.9% of other MSM were seropositive for any 4vHPV types, only 29.5% of HIV-positive MSM and 8.5% of other MSM were seropositive for all four 4vHPV types of HPV. 23 These findings suggest that sexually active young MSM can benefit from vaccination.…”
Section: Discussionmentioning
confidence: 94%
“…22 However, a recent study among 922 vaccine-eligible gay, bisexual, and other MSM aged 18–26 years in 2 US cities demonstrated that while 90.9% of HIV-positive young MSM and 62.9% of other MSM were seropositive for any 4vHPV types, only 29.5% of HIV-positive MSM and 8.5% of other MSM were seropositive for all four 4vHPV types of HPV. 23 These findings suggest that sexually active young MSM can benefit from vaccination.…”
Section: Discussionmentioning
confidence: 94%
“…Since 2011, the Advisory Committee on Immunization Practice (ACIP) recommended routine vaccination for all males at ages 11‐12 years, through age 21 years for men not previously fully vaccinated, and through age 26 years for MSM and immunocompromised men, including those with HIV infection . Quadrivalent HPV vaccination of MSM was likely reported as an effective and cost‐effective way for reducing the burden of HPV‐related disease in MSM .…”
Section: Discussionmentioning
confidence: 99%
“…35 Since 2011, the Advisory Committee on Immunization Practice (ACIP) recommended routine vaccination for all males at ages 11-12 years, through age 21 years for men not previously fully vaccinated, and through age 26 years for MSM and immunocompromised men, including those with HIV infection. [36][37][38] Quadrivalent HPV vaccination of MSM was likely reported as an effective and cost-effective way for reducing the burden of HPV-related disease in MSM. 39,40 Particularly Current evidences support to achieve the target of universal vaccination with a gender-neutral approach by considering both HPV vaccination's clinical effectiveness and economic sustainability.…”
Section: Genotype Distribution In Hpv Positive Msmmentioning
confidence: 99%
“…Detailed methods have been reported previously. 30 Enrollment occurred at 3 clinical facilities providing sexually transmitted disease (STD), HIV, and other clinical care to lesbian, gay, bisexual, and transgender (LGBT) populations in 2 US cities: Chicago, IL (n = 328 [32%]) and Los Angeles, CA (n = 705 [68%]) during July 2012 to August 2014. In Chicago, 7.5% (29/384) of those invited and age eligible refused; and in Los Angeles, 4.4% (35/791) of those invited and age eligible refused.…”
Section: Methodsmentioning
confidence: 99%